Challenges in diagnosis and health care in polycystic ovary syndrome in Canada: a patient view to improve health care - Beate C. Sydora; Michaelann S. Wilke; Maggie McPherson; Sarah Chambers; Mahua Ghosh; Donna F. Vine (BMC, 2023)
Abstract Background Polycystic Ovary Syndrome (PCOS) is the most common endocrine-metabolic disorder affecting health and quality of life of those affected across the lifespan. We currently have limited evidence-based data on the experience of those living with PCOS in the health care system including diagnosis, health concerns and disease management. The aim of this study was to assess the perceptions of health status, health care experience and disease management support in those affected by PCOS in Alberta, Canada. Methods An online questionnaire was completed via REDCap by individuals self-reporting a diagnosis of PCOS. Question categories included demographics, symptoms of PCOS and time to confirm a diagnosis, follow-up care, health concerns, and information resources. Descriptive statistics were used and thematic analyses was applied to open-response questions. Results Responses from 194 participants living in Canada (93% in Alberta) were included. The average age was 34 ± 8 years and BMI was 35 ± 9. Menstrual irregularity was identified in 84% of respondents as the first symptom noticed and the primary reason for seeking a medical consultation. A PCOS diagnosis occurred on average 4.3 years following awareness of first symptoms and required consultation with more than one primary care provider for 57% of respondents. Half (53%) of respondents reported not receiving a referral to specialists for follow-up care and 70% were not informed about long-term health morbidity such as diabetes or cardiovascular disease. Most respondents (82%) did their own research about PCOS using on-line sources, academic literature and advice from peer support. The participant themes from open questions for improving health care included more resources and support, increased and reliable information, better education and training for clinicians, timely diagnosis, prompt referrals to specialists, and generally more compassion and empathy to the challenges faced by those managing their disease. Conclusion Our findings highlight the health concerns and challenges in health care for those with PCOS. In Alberta, Canada we have identified major gaps in health care including a timely diagnosis, follow up care and supports, and multidisciplinary care. This evidence-based data can be used to inform development of pathways to improve the health care experience in those affected by PCOS.